Ecological Impacts of Mining Activities: Local Knowledge of Bajo Fisherman Communities - Takwa Takwa; Zakaria Zakaria; Hendri Yawan; Ashari Ashari; Sumarlin Rengko HR; Muh Nurtanzis Sutoyo (English Education Study Program, 2023)
This study aims to determine the extent of ecological changes affecting the fishermen in the coastal area of Pomalaa District, Kolaka Regency, and how the local knowledge of the Bajo fishermen in Kolaka manifests. The results of the study indicate that the ecological changes in the coastal area are caused by massive nickel mining activities on the coast, which have an impact on the lives of fishermen in the coastal villages of Pomalaa District, namely Hakatutobu, Tambea, Sopura, and Oko-Oko villages. The forms of ecological changes are evident in the pollution of the environment in mangroves, seagrass beds, coral reefs, and other marine biota, even the damages to the community's fisheries cultivation such as sea cucumber, seaweed, and floating cage culture. The study also found that the Bajo fishermen's community is very dilemmatic in facing this reality, and there is no choice for fishermen other than to rely on their local knowledge, search for and catch marine products as their effort to meet their needs.